Field report PAC 671: Raki CS Tan & Ramanan / Akmal Hakim Mohd Hafiz - Mohd Hafiz, Akmal Hakim (Universiti Teknologi MARA, Terengganu, 2023)
Raki CS Tan & Ramanan is a distinguished audit and assurance firm renowned for its commitment to excellence and integrity in financial services. Established with a vision to provide unparalleled audit solutions, the firm has accumulated decades of experience serving a diverse clientele across various industries. Through their dedication to precision and professionalism, they have emerged as a trusted partner for organizations seeking rigorous financial oversight and strategic guidance. They have a total of 5 branches in Malaysia which are located at Kuala Lumpur for the head office, Johor Bahru, Melaka, Kota Kinabalu and Kuching for the offices.